Jason and the Argonauts : a retelling - Gunderson, Jessica; Takvorian, Nadine (Mankato, MN : Picture Window Books, 2012)
An illustrated retelling of the classic Greek myth, in which Jason and the Argonauts are sent on a quest for King Pelias, to capture the Golden Fleece, but after years of sailing, Jason must succeed in a series of trials before he can claim his prize.
Includes bibliographical references (p. 32).
Library Media Connection starred
Library Media Connection starred, March 2012
4.1
3-6.
3-6
Keywords: Argonauts (Greek mythology) -- Juvenile literature; Jason (Greek mythology) -- Juvenile literature; Argonauts (Greek mythology); Jason (Greek mythology); Argonauts (Legendary characters); Jason (Legendary character)